Comunidades bentônicas recifais do Atlântico Sul Ocidental: estrutura, distribuição espacial e influência de variáveis ambientais - Santana, Erika Flávia Crispim de (2020)
Brazilian reefs are unique in the world due the high abundance of fleshy macroalgae and turf algae and low richness of reef-building corals. Environmental (e.g. seawater temperature, light availability) and spatial drivers (e.g. depth, offshore distance) are responsible for structuring the benthic marine communities. It is believed that shallow to mesophotic reefs are differently influenced by abiotic drivers, particularly light and temperature, which limit/modify the organisms’ occurrence and abundance on reefs. While few Brazilian corals prefer shallow waters with high temperatures and direct incidence of light, but most of them show preference for turbid waters and deeper zones, as they uptake attenuated light. Considering this, the present study used powerful classifications tools to address the following aims: 1) to identify and boundary discrete shallow benthic communities (0-30m) in coastal and oceanic reefs, as well as identifying their main environmental drivers, 2) to determine the threshold (i.e. transition) between shallow and deep benthic communities (30- 60m), using the Brazilian oceanic islands as a model and 3) to understand the influence of local biotic (i.e. contact interactions) and environmental factors on the large-scale patterns of basal bleaching (i.e. out of years with anomaly) of the three most abundant and important reef-building corals in Brazil Siderastrea spp., Mussismilia hispida e Montastraea cavernosa. As a result, benthic communities and environmental variables (remote-sensing data) were obtained for 18 sites (14 coastal and 4 oceanic), representing the most complete database of abundance of benthic reef organisms for Brazil. Ten distinct benthic communities were identified for both coastal and oceanic reefs, which are dominated by turf algae and fleshy macroalgae. The turbidity was the main environmental driver responsible for the two types of shallow reef communities: i) in warm waters reefs (dominated by macroalgae), ii) another with turbid water (dominated by turf algae). Geographical drivers also influenced the distribution of shallow and mesophotic benthic communities. Depth and temperature had a significant influence on the distinction between shallow reef and mesophotic benthic communities at the oceanic islands, with five distinct communities being identified. The threshold between the shallow and deep communities was 12.5 m, and no significant changes were recorded up to 30 m depth, as previously indicated. The highest incidence of coral bleaching occurred in shallow and well-illuminated (euphotic) oceanic reefs, corroborating the preference of the most corals for shaded coastal and/or deep habitats. The results showed that the use of classification tools is useful for studies of benthic reef communities along the large spatial scales and for understanding the environmental drivers governing them. In addition, they provide important data on the health of Brazilian corals in years without thermal anomalies, which represent an important baseline for future assessments of the impacts caused by mass bleaching events in the Southwestern Atlantic reefs.